ANALISIS KINERJA KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH PROVINSI JAWA TIMUR - Chintya Nabella Asharini; Dyah Ratnawati H; Gideon Setyo Budiwitjaksono (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
New Public Management provides consequences for local governments to implement performance-based budgets with a mechanism that that follows good planning, implementation and control stages. Capital Expenditure Growth is an indicator of the performance of Regional Work Units (SKPD), which currently shows a growth rate that is less than optimal. Value For Money is a guideline for financial management towards achieving SKPD performance. This research aims to examine Value For Money, namely Economic factors, Efficiency and Effectiveness on Financial Performance in SKPD East Java Province. This research uses a quantitative approach with the object of the Budget Realization Report and uses a sample of 10 Regional Work Unit in East Java Province during the 2017-2020 period, and uses a purposive technique based on predetermined criteria. The research results show that Value for Money, which consists of economic factors, efficiency and effectiveness, together has an influence on Financial Performance. Individually, economic factors have a negative influence on financial performance. Meanwhile, the Efficiency and Effectiveness factors have no influence on Financial Performance.